Design of Hybrid Solar Power Plant for household Electricity Loads 1300 VA - Bambang Winardi; Enda Wista Sinuraya; Agung Nugroho; Erlin Dolphina (International Journal of Basic and Applied Science, 2022)
Indonesia is a country that is rich in sunshine. Based on NASA's Power Data Access Viewer data in 2021, Indonesia has an average radiation level of 5.6 kWh/m2/day. This situation is a big advantage for Indonesia in utilizing solar energy into electrical energy through photovoltaic, especially in the Semarang City area which has an average radiation level of 5.6 kWh/m2/day. The house where the research is located is in Pudakpayung, Semarang City with a roof area of ​​24m2. The Hybrid Solar Power Plant that is designed is an electric power supply system whose sources come from the Solar Power Plant and the State Electricity Company alternately which are regulated automatically by automatic control equipment with battery capacity mode. The results of the calculation, the required components consist of 9 solar modules with a capacity of 120 WP, 4 batteries with a capacity of 12v100Ah, 1 unit of 3000 Watt inverter and 1 unit of Solar Charger Controller 60A. The results of the tests that have been done, the solar panels produce an average power of 5446 wh per day, the battery will be full at 13.00.